Rediscovering the relevance of clinical medicine with a case of Chilaiditi’s syndrome - Saha, Aritra; Rahman , Sofiur; Pegu , Ajit Kumar; Ozah , Jinku; Thakuria , Mayuree (Indian Journal of Case Reports, 2024)
Chilaiditi’s sign is a rare radiological diagnosis characterized by colonic interposition between the diaphragm and the liver, and when symptomatic it is known as Chilaiditi’s syndrome. We report that the case of a 55-years-old male, who was referred to our institution as a case of colitis, with the symptoms of recurrent vomiting, pain abdomen, and altered bowel habit, was eventually diagnosed to have Chilaiditi’s syndrome with non-specific colitis, after carefully taking the history and clinically examining the patient.